Pomalidomide plus low‐dose dexamethasone in relapsed refractory multiple myeloma after lenalidomide treatment failure. (6th October 2019) - Siegel, David S.; Schiller, Gary J.; Song, Kevin W.; Agajanian, Richy; Stockerl‐Goldstein, Keith; Kaya, Hakan; Sebag, Michael; Samaras, Christy; Malek, Ehsan; Talamo, Giampaolo; Seet, Christopher S.; Mouro, Jorge; et al.
Summary: Patients with relapsed/refractory multiple myeloma (RRMM) for whom the benefits of lenalidomide have been exhausted in early treatment lines need effective therapies. In cohort A of the phase 2 MM‐014 trial, we examined the safety and efficacy of pomalidomide plus low‐dose dexamethasone immediately after lenalidomide‐based treatment failure in patients with RRMM and two prior lines of therapy. Pomalidomide 4 mg was given on days 1 to 21 of 28‐day cycles. Dexamethasone 40 mg (20 mg for patients aged >75 years) was given on days 1, 8, 15 and 22 of 28‐day cycles. The primary endpoint was overall response rate (ORR), and secondary endpoints included progression‐free survival (PFS), overall survival (OS) and safety. The intention‐to‐treat population comprised 56 patients; all received prior lenalidomide (87·5% lenalidomide refractory) and 39 (69·6%) received prior bortezomib. ORR was 32·1% (28·2% in the prior‐bortezomib subgroup). Median PFS was 12·2 months (7·9 months in the prior‐bortezomib subgroup). Median OS was 41·7 months (38·6 months in the prior‐bortezomib subgroup). The most common grade 3/4 treatment‐emergent adverse events were anaemia (25·0%), pneumonia (14·3%) and fatigue (14·3%). These findings support earlier sequencing of pomalidomide‐based therapy in lenalidomide‐pretreated patients with RRMM, including those who have become refractory to lenalidomide. Trial registration: www.ClinicalTrials.gov identifier NCT01946477.